Longitudinal analysis of morbidity and mortality due to septicemia and comparison with number of beds in Brazilian states - Pereira, Ana Laura Pelissaro; Rodrigues, Beatriz Orlandi; Kock, Kelser de Souza (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Sepsis is a serious organic dysfunction triggered by the body’s unregulated response to infection, with globally increasing morbidity and mortality rates. In Brazil, challenges such as inequality in bed availability affect management. Aim: To analyze morbidity and mortality due to sepsis in 2012 and 2022 in Brazilian states, relating them to the number of hospital beds. Outlining: ecological time series study, with data collected from DATASUS. The dependent variables were morbidity and mortality and lethality due to septicemia, and the independent variables included time and number of beds. Results: A significant increase in morbidity and mortality cases was observed in Brazil and in most Brazilian states. The average lethality was 45.09%, with extremes in Rio de Janeiro (58.2%) and Roraima (25.9%). Analysis by age range showed an increase with age and similarity between genders. Significant positive correlations were demonstrated between number of beds and morbidity and mortality and negative correlation with lethality. Implications: this study provides the basis for implementing measures that aim to improve the care and prevention of septicemia in Brazil, inferring that states with a greater number of hospital beds have better quality and access to care and, therefore, greater diagnostic and treatment capacity.